The simplest unified growth theory - Holger Strulik; Jacob Weisdorf (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2007)
This paper provides a uni?ed growth theory, i.e. a model that explains the very long-run economic and demographic development path of industrialized economies, stretching from the pre-industrial era to present-day and beyond. Making strict use of Malthus' (1798) so-called preventive check hypothesis that fertility rates vary inversely with the price of food the current study o?ers a new and straightforward explanation for the demographic transition and the break with the Malthusian era. The current framework lends support to existing uni?ed growth theories and is well in tune with historical evidence about structural transformation.
Keywords: O11; O14; J10; J13; 330; Economic Growth; Population Growth; Structural Change; Industrial Revolution; Wachstumstheorie; Bevölkerungsökonomie; Bevölkerungstheorie; Entwicklung; Strukturwandel; Industrialisierung; Demographischer Übergang; Theorie